Factors Affecting Share Prices With the Role of Capital Structure as Intervening - Andriani, Ratih; Rita Yunita Resmi; Dewi Widiarti (Sekolah Tinggi Teknologi Wastukancana, 2025)
This research aims to analyze the influence of profitability, asset structure, sales growth, and interest rates on stock prices with capital structure as an intervening variable. The research object takes companies that are included in the LQ45 index. The sampling method used is purposive sampling. With the established criteria, 16 companies were obtained as the research sample. The variables used are profitability proxied by Return On Equity (ROE), asset structure, sales growth, interest rates proxied by Bank Indonesia Certificates (SBI), capital structure proxied by Debt to Equity Ratio (DER), and stock price. The data analysis technique used is path analysis.Based on the research results, it shows that partially only profitability affects stock prices. Simultaneously, profitability, asset structure, sales growth, and interest rates together affect stock prices by 12.3%, while profitability, asset structure, sales growth, and interest rates simultaneously affect capital structure by 15.6%. Based on path analysis, capital structure weakens the effect of profitability on stock prices, capital structure weakens the effect of asset structure on stock prices, capital structure weakens the effect of sales growth on stock prices, and capital structure weakens the effect of interest rates on stock prices.